Management of Gingival Hyperpigmentation by Scalpel Technique: A Case Report - Gina Dhiya Salsabila; Sulistiawati; Ifadah (Sriwijaya Journal of Dentistry, 2025)
Introduction: Gingiva is a mucous membrane that is closely attached to the periosteum of the jaw. The color of the gingiva varies, it ranges from pink to dark brown. Melanin is the most common natural pigment that contributes to endogenous gingival pigmentation. The degree of pigmentation depends on a few factors. This gingival hyperpigmentation is considered a normal variation, but the discoloration is aesthetically displeasing to some patients. Thus, surgical intervention may be necessary. Purpose: Report the procedure of gingival depigmentation using a scalpel in a 39-year-old woman with gingival hyperpigmentation.. Case presentation: A 39-year-old female visited the Hospital complaining that her upper front gums were dark brown since 1 year ago. Clinical examination showed brown discoloration of the anterior attached gingiva of the upper and lower jaws. Based on clinical and radiographic examinations, the patient was diagnosed with generalized chronic periodontitis accompanied by gingival hyperpigmentation in the anterior maxilla and mandible. In the nonsurgical phase, scaling was carried out, oral hygiene education was performed. After that, gingival depigmentation surgery was performed using the scrapping technique. Follow-up was carried out after surgery. Satisfactory results were obtained, marked by the clinical appearance, rapid healing and the patient felt comfortable with minimal pain during the healing process. Conclusion: Scalpel technique is one of the procedures performed in cases of gingival hyperpigmentation. This technique can restore the aesthetics of the patient's gingiva in a simple, safe and non-invasive way and shows satisfactory results and has a fast wound healing time. Keywords: Gingival hyperpigmentation; periodontal surgery; scalpel technique